Vegetative Establishment Rate and Stolon Growth Characteristics of 10 Zoysiagrasses in Southern Europe - Pompeiano, Antonio; Grossi, Nicola; Volterrani, Marco (HortTechnology (Alexandria, Va.), 2012)
In today's climate, in which economic and environmental sustainability has to be ensured, it is important to promote the use of grass species that require minimal maintenance inputs. The superior heat and drought tolerance of zoysiagrass ( Zoysia spp.) makes it an excellent choice for Mediterranean areas. A study was conducted to evaluate the establishment rate from vegetative plugs of 10 zoysiagrass genotypes (i.e., species and cultivars). Stolon growth rate, establishment rates, biometric traits, and winter color retention were measured. Establishment rate was measured using digital image analysis, and the data were fit to a sigmoid variable slope model. Zoysiagrass genotype significantly affected turf coverage during the establishment. At 140 days after plugging, ‘DALZ0101’ and ‘Zenith’ had significantly more turfgrass coverage, while ‘Emerald’, ‘HT-210’, ‘Meyer’, and mascarene grass ( Zoysia pacifica ) had the lowest coverage. Differences in total stolon length and growth rate were observed among the genotypes and for all stolon growth parameters. Japanese lawn grass ( Zoysia japonica ) had higher values compared with manilagrass ( Zoysia matrella ). A distinct trend in days to maintained 50% color retention (Days 50 ) was observed in this study on the winter color retention of genotypes. Differences in color retention within japanese lawn grass cultivars were observed with ‘Victoria’ retaining color longer than ‘DeAnza’ and ‘El Toro’ (77.6, 57.8, and 57.2 Days 50 , respectively) and better than ‘Meyer’. Japanese lawn grass cultivars exhibited poor color retention (50.3 Days 50 ) compared with manilagrass cultivars (79.3 Days 50 ).